The role of strain partitioning on intermontane basin inception and isolation, External Western Gibraltar Arc. (December 2015) - Jiménez-Bonilla, A.; Expósito, I.; Balanyá, J.C.; Díaz-Azpiroz, M.; Barcos, L.
Highlights: In the Ronda Basin area pre-basin and basin-related deformation is characterized. The basin is generated by an overall post-Serravallian NE–SW arc-parallel stretching. The basin was isolated from its foreland basin by a transpressive structural high. Qualitative and quantitative geomorphic analysis suggest a Plio-Quaternary activity. Strain partitioned into NW–SE shortening, NE–SW extension and dextral transpression. Abstract: The intermontane Ronda Basin, currently located in the Western Betics External Zones, started as an embayment of the Betic foreland basin during the Tortonian. We have characterized a post-Serravallian, basin-related deformation event that overprinted the former fold-and-thrust belt. Updated structural and kinematic maps allow us to identify NW–SE basinward-dipping normal faults at the southwestern and northeastern boundaries of the basin and NE–SW shortening structures (large-scale folds and reverse faults) affecting both the outcropping basement and partially the basin infill. In order to test the possible tectonic activity of these structures during the last 5 Ma, exhaustive geomorphologic analyses in the Ronda Basin area have been done. This included the qualitative study of relief and drainage network, together with the characterization of quantitative indices (SLk, Smf, V f and HI). These results obtained from this analysis are coherent with structural data and suggest that the identified post-Serravallian structures were active up to at least 5 Ma. We also conclude that the Ronda Basin was generated by along strike segmentation of the relief in the Western Betics induced by NE–SW (arc-parallel) stretching accompanied with NW–SE shortening. In the NW basin boundary, the strain was partitioned into ENE–WSW dextral strike-slip faults and NE–SW shortening structures, which gave rise to a Messinian transpressive structural high that disconnected the former Ronda Basin from its parental foreland basin.